(untitled) (TAJ: Journal of Teachers Association, 2021)
Background: Amebic liver abscess (ALA) is an ancient parasitic disease caused by E. histolytica described first by Hippocrates. It is endemic worldwide, mainly in tropic and subtropics countries. About 50 million true E. histolytica infections and approximately 100,000 deaths occur each year globally. In Bangladesh, exact incidences of amebic liver abscess cases are not estimated, but hospital reports indicate that it is endemic. Immunity and immune responses in acute and post infections of ALA are not well understood to date. However, the understanding of immunology is essential to know disease progression, recovery, morbidity, and mortality as well as diagnosis and newer prevention strategies like vaccine development. In this 15-month prospective and follow-up study, different antibody responses are estimated periodically. Methods: About 90 amebic liver abscess patients diagnosed initially by ultra-sonogram confirmed followed by Real-Time PCR were selected for this study. All were admitted into Rajshahi Medical College Hospital, Bangladesh. Antibody responses against different antigens, which include Serum anti-lectin IgG, Salivary anti-CRD (carbohydrate recognition domain) Ig A, and Stool anti-CRD (carbohydrate recognition domain) IgA were estimated by ELISA periodically thrice, in acute stage after 06 and 09 months and between 12 and 15 months. Results: Serum anti-lectin IgG in ALA persists remarkably high well up to 09 months in 98% cases, Secretory anti-CRD IgA was also determined from the saliva, and only 36(40%) show positive titer during first 06 months, and about 40% of ALA cases show high titer of anti-CRD IgA from stool samples in first six months of infection. Conclusion: Only serum anti lectin Ig G showed significant high titer in 98% of cases in the acute stage and up to nine months of infection. TAJ 2021; 34: No-1: 05-08